Students’ engagement in digital mind mapping-supported collaborative learning during the post-pandemic era - Nara Sari; Ayu Liskinasih; Mihiri Ianthi Jansz (Jurnal Inspirasi Pendidikan, 2023)
Previous research has demonstrated the effectiveness of digital mind-mapping in improving student learning outcomes, creativity, critical thinking skills, and motivation. However, past studies rarely focused on student engagement when exploring the implementation of collaborative digital mind mapping in higher education. This study explored student engagement in a digital mind-mapping-supported collaborative classroom. The study was qualitative descriptive in nature, involving twenty fourth-semester students from a private university in Indonesia. The data were collected through observation and interview. The findings showed that students engaged cognitively, emotionally, and behaviorally in the collaborative mind-mapping activity. The findings mostly describe student-student and student-task engagement. Therefore, further investigations are needed to examine student-teacher engagement in a mind-mapping-supported collaborative learning setting.